Cultura e educação: saberes e fazeres de professoras da educação infantil - Souza, Bárbara Ondina Monteiro de (2018)
This qualitative research aimed to analyze the knowledge and actions presented by teachers of early childhood education about the culture of São José. The research was carried out with five teachers of a Center for Early Childhood Education of the public network of the municipality of São José. Data collection was done from a written narrative about "an imaginary walk through the city to know its culture" and a questionnaire constituted for 19 open questions about the topic. The study showed that they demonstrated an awareness of the importance of transmitting knowledge related to the local culture to the children, considered by them as subjects of future generations; understand that their work should be complementary to that of families; emphasize the importance of the history related to the arrival of the Azoreans, value the material cultural heritage - architectural - of the center of the city where the Center for Early Childhood Education is located, mentioning the Bica da Carioca, Matriz, the Museum, the library and the local theater , without, however, exploiting more intensely the legends, myths, causes, etc., also inherited from the Portuguese. They are not unanimous in thinking that the media, mediators of "globalization", only bring harmful effects to the population, and wish that the cultural week will actually be implemented in the Center for Early Childhood Education. For their part, they were confused about celebrations of the festive dates in the Early Childhood Centers and cited the infrastructure needs that would enable them to explore the city more with the children; such as lack of transport and security.